2014
DOI: 10.1590/s2317-64312014000400001426
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the profile of speech-language therapists from Paraná and Santa Catarina from 2000 to 2011

Abstract: Purpose Comparative analysis of the profile of speech-language therapists that work in the states of Paraná and Santa Catarina in 2000 and 2011. Methods application of a questionnaire that considered the following variables: identification of data, undergraduates and graduates, professional aspects. The responses obtained in 2000 and 2011 were compared by means of the difference of proportions test, with a significance level of 5%. Results The comparison of the data has shown that: the number of speech-languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Regarding the age of the professionals, in other studies it has been observed an average age over 30 years, at the time the research was conducted (15)(16)(17)(18)(19)(20)22) and only two studies with speech therapy graduates reported average age within the range of 20 to 30 years (9,13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the age of the professionals, in other studies it has been observed an average age over 30 years, at the time the research was conducted (15)(16)(17)(18)(19)(20)22) and only two studies with speech therapy graduates reported average age within the range of 20 to 30 years (9,13) .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the egresses were mostly female up to 29 years old. Studies have shown that speech therapy profession is mostly undertaken by female professionals (9,(15)(16)(17)(18)(19)(20)(21)(22) . One author relates this occurrence to the fact that women are more maternally oriented, transferring to the professional practice the tasks related to the care of another person (23) .…”
Section: Discussionmentioning
confidence: 99%